Case Report: A rare case of familial lung cancer requiring pneumonectomy in three male siblings - Kaprin, Andrey; Pikin, Oleg; Ryabov, Andrey; Aleksandrov, Oleg; Toneev, Evgeniy; Lubchenko, Ludmila; Zelenova, Ekaterina (Frontiers in Oncology, 2022)
Lung cancer is a disease with a unique genetic pattern and is occasionally related to hereditary syndromes such as Lynch, Louis–Bar, and Li–Fraumeni. In some patients, germinal mutations may be discovered in combination with somatic alterations. For instance, Li–Fraumeni syndrome often reveals a mixture of TP53 and EGFR mutations. The development of new target therapies necessitates an extensive search for new pathogenic mutations. In this article, we present a rare case report of lung cancer, requiring a pneumonectomy, in three sibling brothers.